Advancing Pediatric Psychiatry Research: Linking Neurobiological Processes to Novel Treatment and Diagnosis Through the Research Domain Criteria (RDoC) Project. (September 2015) - Drury, Stacy; Cuthbert, Bruce
The concurrent release of the Diagnostic and Statistical Manual, 5th Edition (DSM-5) and the National Institute of Mental Health (NIMH) Research Domain Criteria (RDoC) project both ignited controversy and raised clarifying questions, particularly related to their integration and utility in both research and clinical domains. As the initial debate quieted, it appeared that DSM-5 would reign in clinical practice and RDoC would take precedence in research. DSM-5 and RDoC, while theoretically different, have analogous goals, as both seek to improve the accuracy of diagnosis, advance treatments, and decrease morbidity from mental illness. To achieve these goals, clinicians and researchers must, at the earliest stages of RDoC, work together to ensure maximum clinical translation. Other areas of medicine have successfully leveraged enhanced molecular and neurobiological phenotypic specificity to refine treatments and design novel pharmacologic agents. These successes provide useful comparisons for child psychiatry in the era of RDoC and DSM-5. This article reviews the literature related to progress in child psychiatry, development of RDoC, and the role of genetic research in the advancement of other areas of medicine. Limited diagnostic and treatment advances have occurred in child psychiatry over recent decades, particularly in comparison to other medical fields. The rapidly evolving fields of molecular genetics, neurobiology, and behavioral science offer substantial promise for refining diagnosis and treatment modalities. Utilizing the advancement of care for other pediatric conditions such as cystic fibrosis and pediatric cancer as guides, this article outlines how RDoC may contribute to similar advancements for pediatric mental illness. Although requiring a paradigm shift and the building of novel transdisciplinary collaborations that incorporate clinicians, basic scientists, pharmaceutical companies, families and advocacy groups, the integration of RDoC into child psychiatry clinical research offers significant potential to advance diagnostic specificity, improve treatment, and decrease mental health stigma.